Study of antiemetic pattern on cancer patients with cancer by cytostatic therapy hospitals in Yogyakarta - Perwitasari, Dyah Aryani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The aim of the research was to know the description of antiemetic usage on the patients with cancer based on the medical records that were available in the hospital. Hereby, the use of antiemetic would be compared to literature for seeing the pattern.The study was a descriptive, analytic and retrospective study. The data taken from the medical records were written by doctor and nurses for cancer in patients hospital during Januari to June 2003. Data were grouped based on cytotoxic treatment with strong, medium and weak emetogenic effects, the condition of cancer patients, and antiemetic usage before and after having cytotoxic treatment.The results showed antiemetic usage before and after strong emetogenic cytotoxic treatment were not suitable because there was no combination with dexametason. Antiemetic usage which was used before and after mild emetogenic cytotoxic treatment were not suitable with ondansetron, metochlorpramide, combination of ondansetron – metochlorpramide. The use of antiemetic on cancer patients who got strong and medium emetogenic cytostatic was not been suitable with literatures because the patients were not given dexamethasone as combination therapy. For cancer patients given before and after medical treatment with weak emetogenic effect weren’t suitable in both of hospitals. Antiemetic usage before cytotoxic treatment that was not suitable was ondansetron and metoclopramide, where as antiemetic usage after cytotoxic that was suitable was metoclopramide.Key words: Antiemetic, Emetogenic Effect, Cytotoxic, hospital